Clinical and biomechanical perspectives on pressure injury prevention research: The case of prophylactic dressings. (October 2016) - Gefen, A.; Kottner, J.; Santamaria, N.
Abstract: In this perspective paper, we discuss clinical and biomechanical viewpoints on pressure injury (or pressure ulcer) prevention research. We have selected to focus on the case of prophylactic dressings for pressure injury prevention, and the background of the historical context of pressure injury research, as an exemplar to illuminate some of the good and not so good in current biomechanical and clinical research in the wound prevention and care arena. Investigators who are conducting medical or clinical research in academia, in medical settings or in industry to determine the efficacy of wound prevention and care products could benefit from applying some basic principles that are detailed in this paper, and that should leverage the research outcomes, thereby contributing to setting higher standards in the field. Highlights: Discuss clinical and biomechanical viewpoints on pressure injury prevention research Focus on the case of prophylactic dressings for pressure injury prevention Illuminate the good and not so good in current biomechanical and clinical research in wound care